2018
DOI: 10.1111/jcmm.13984
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between phospholipids and insulin resistance: From clinical to experimental studies

Abstract: Insulin resistance induced by high‐fat diet and impropriate life style is a major contributor to the pathogenesis of metabolic disease. However, the underlying molecular mechanisms remain unclear. Recent studies in metabolic dysfunction have extended this beyond simply elevated cholesterol and triglycerides levels and have identified a key role for lipid metabolism. For example, altered phospholipid metabolism has now become central in the pathogenesis of metabolic disease. In this review, we discuss the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 91 publications
4
54
1
Order By: Relevance
“…In a recent study in non-human primates, Polewski et al identified differences in plasma phospholipid composition, most notably perturbations in diacylglycerols that are desaturation products of palmitic acid, as markers of worsening insulin resistance and onset of the metabolic syndrome [56]. While the specific metabolites identified differed from those of the present study, phospholipids are integral components of the cell membrane and plasma and their metabolism influences numerous biochemical pathways, including those involved in glycaemic regulation [57]. The compounds of particular interest in Factor 4 include diacylglycerol derivatives of palmitoleic acid (e.g., palmitoleoyl-linoleoyl-glycerol [16:1/18:2]), an unsaturated monounsaturated fatty acid that has been found to exhibit similar detrimental effects to palmitic acid on cardiovascular traits in adult men [58].…”
Section: Statement Of Principal Findingscontrasting
confidence: 49%
“…In a recent study in non-human primates, Polewski et al identified differences in plasma phospholipid composition, most notably perturbations in diacylglycerols that are desaturation products of palmitic acid, as markers of worsening insulin resistance and onset of the metabolic syndrome [56]. While the specific metabolites identified differed from those of the present study, phospholipids are integral components of the cell membrane and plasma and their metabolism influences numerous biochemical pathways, including those involved in glycaemic regulation [57]. The compounds of particular interest in Factor 4 include diacylglycerol derivatives of palmitoleic acid (e.g., palmitoleoyl-linoleoyl-glycerol [16:1/18:2]), an unsaturated monounsaturated fatty acid that has been found to exhibit similar detrimental effects to palmitic acid on cardiovascular traits in adult men [58].…”
Section: Statement Of Principal Findingscontrasting
confidence: 49%
“…Phosphatidylcholine (PC) and phosphatidylethanolamine (PE) are major components of cellular membranes where they are involved with essential cellular processes (1,2). PC and PE are synthesized de novo by CDP-Cho and CDP-Etn branches of the Kennedy pathway in which the extracellular substrates choline (Cho) and ethanolamine (Etn) are actively transported into the cell, phosphorylated and coupled with diacylglycerols (DAG) to form the final phospholipid product.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alterations in the fatty acid composition of glycerophospholipids has been associated to decreased insulin sensitivity. 19 The association between non-bilayer lipids, like palmitoyloleoyl PE (POPE, compound 3) and glucose metabolism has been previously demonstrated, since POPE increases GLUT4 activity, increasing glucose uptake. 20 Accordingly, this phospholipid was significantly (P < .05) lower in all DFU groups as compared to no T2DM (control) group (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, alterations in the fatty acid composition of glycerophospholipids has been associated to decreased insulin sensitivity. 19 …”
Section: Discussionmentioning
confidence: 99%